Evolution of bridge frequencies and modes of vibration during truck passage. (1st December 2017) - Cantero, Daniel; Hester, David; Brownjohn, James
Highlights: Experimental evidence of modal property changes in vehicle-bridge systems. Changes in shape of mode of vibration reported for the first time. Theoretical interpretation of results through a simplified model. Improved visualization in time–frequency domain of acceleration signals. Abstract: This paper reports an experimental campaign that aims at measuring the evolution of bridge modal properties during the passage of a vehicle. It investigates not only frequency shifts due to various vehicle positions, but also changes in the shape of the modes of vibration. Two different bridges were instrumented and loaded by traversing trucks or trucks momentarily stationed on the bridge. The measurements were analysed by means of an output-only technique and a novel use of the continuous wavelet transform, which is presented here for the first time. The analysis reveals the presence of additional frequencies, significant shifts in frequencies and changes in the modes of vibration. These phenomena are theoretically investigated with the support of a simplified numerical model. This paper offers an interpretation of vehicle-bridge interaction of two particular case studies. The results clearly show that the modal properties of the vehicle and bridge do change with varying vehicle position.